Bifunctional N‐Heterocyclic Carbene Ferrocenyl Ligands – Synthesis and Palladium(II) Complexes. Issue 4 (9th January 2015) - Loxq, Pauline; Daran, Jean‐Claude; Manoury, Eric; Poli, Rinaldo; Labande, Agnès
Abstract: Two ferrocenylimidazolium tetrafluoroborate salts [R = Me, 7 and R = (2, 4, 6‐trimethylphenyl), 8 ], precursors of new ferrocenylimidazol‐2‐ylidene bifunctional ligands, have been prepared for the first time. The free 1‐(2‐dimethylaminomethyl)ferrocenyl‐3‐methylimidazol‐2‐ylidene (12 ) was isolated and characterised by 1 H and 13 C NMR spectroscopy and represents the second example of an isolated and characterised imidazol‐2‐ylidene directly linked to ferrocene. Neutral (compound13 ) and cationic (compound14 ) palladium(II) complexes were obtained in moderate yields and characterised by 1 H and 13 C NMR spectroscopy and mass spectrometry. Abstract : Two ferrocenylimidazolium tetrafluoroborate salts, precursors of new ferrocenylimidazol‐2‐ylidene bifunctional ligands, and the corresponding palladium(II) complexes have been prepared for the first time.